A mesoscale in situ method for assessing fracture toughness of intra-yarn and interface in 3D woven composites. (16th June 2022) - Sun, Ruijian; Li, Zhixing; Guo, Licheng; Yu, Hongjun; Zhang, Li; Zong, Qingsong
Abstract: Accurate acquisition of mesoscale in situ properties of 3D woven composites (3DWC) is necessary for characterizing damage behavior and strength. However, it is difficult and very limited studies have been conducted. In this paper, a mesoscale in situ (MIS) method is proposed to assess fracture toughness of intra-yarn and interface in 3DWC. Two types of specimens, interface specimens and intra-yarn specimens, are designed and cut on 3DWC plates, so that they contain typical in situ interface and yarn structures. The thickness, cutting surface, cutting position and notch tip position of both types of specimens, are particularly designed to ensure that the cracks occur in the area of interest. Compact tension experiments are performed to obtain fracture toughness. For intra-yarn specimens, the crack grows inside the weft yarn as expected. The results calculated by the area method and the compliance calibration method show a consistent trend. For interface specimens, the crack passes through the matrix, weft yarn and interface. A modified area method is proposed to remove the energy consumed by the crack segments passing through the matrix and weft yarn. Finally, the possible influence of matrix plasticity is discussed. Graphical abstract: Image 1